2013
DOI: 10.1016/j.jpain.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diets and Thermal Pain: Dissociation of Hypoalgesia, Elevated Ketones, and Lowered Glucose in Rats

Abstract: Ketogenic diets are high-fat, low-carbohydrate formulations effective in treating medically-refractory epilepsy, and recently we demonstrated lowered sensitivity to thermal pain in rats fed a ketogenic diet for 3–4 weeks. Regarding anticonvulsant and hypoalgesic mechanisms, theories are divided as to direct effects of increased ketones and/or decreased glucose, metabolic hallmarks of these diets. To address this point, we characterized the time course of ketogenic diet-induced thermal hypoalgesia, ketosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
4
28
0
Order By: Relevance
“…This outcome was in clear contrast to rats, where the same diet produces these effects reliably. 22, 23 Other mouse strains might produce different results with the hotplate test. Similarly, other tests of thermal pain might be useful to explore diet-induced changes 25 and could further illuminate species differences.…”
Section: The Ketogenic Diet and Thermal Painmentioning
confidence: 99%
See 2 more Smart Citations
“…This outcome was in clear contrast to rats, where the same diet produces these effects reliably. 22, 23 Other mouse strains might produce different results with the hotplate test. Similarly, other tests of thermal pain might be useful to explore diet-induced changes 25 and could further illuminate species differences.…”
Section: The Ketogenic Diet and Thermal Painmentioning
confidence: 99%
“…2A). 23 Therefore, simply raising blood ketones and lowering blood glucose is not sufficient to produce hypoalgesia. This result seems to rule out a mechanism involving, for instance, direct acute effects of ketones on molecular targets underlying thermal pain sensitivity.…”
Section: The Ketogenic Diet and Thermal Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work by Ruskin and colleagues has found that various ketogenic diet formulations resulted in less sensitivity in hot plate tests between 49 and 51°C. 165,166 These authors also noted a reduction in CFA-induced edema in the paw, though allodynia was never measured. 165 However, ketogenic diets were shown to have no effect on neuropathic pain induced by sciatic nerve constriction or paclitaxel injection.…”
Section: Ketogenic Dietsmentioning
confidence: 97%
“…Failure to provide bedding material for a rat to make a nest for her pups can lead to hyperalgesia in those pups when they become adults 55,56 , and the handling of young animals (for example, related to injections, and involving the stress of maternal separation) can cause long-term alterations in pain sensitivity 41,[57][58][59][60][61][62][63] . A growing literature also documents the effect of diet on pain sensitivity [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] . In one case, differences in the soy content of rat chow turned out to be wholly responsible for a failure to replicate in Baltimore the findings of studies originally performed in Jerusalem 65 .…”
Section: Jeffrey S Mogilmentioning
confidence: 99%